PENGALAMAN E-LEARNING SECARA PENUH: PENGGUNAAN EDMODO DALAM KELAS VIRTUAL - Wicaksono, Arief (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2017)
E-learning in full design is believed to be a solution in a digital society. The reality is not entirely correct for granted. This study examines the experience of e-learning in full design at the graduate program the Department of Library and Information Science, University of Indonesia that works for half semester on a single subject. The research method used qualitative research. Data collected by online interviews and online observation. The results showed that virtual classroom using Edmodo proven to increase student participation. However, in practice the advantages of e-learning can backfire for students. The extreme point of the participation in a virtual classroom is done minimally and only to abort obligations.